Caregiver perspectives and preferences for acute otitis media management. Issue 1 (22nd December 2021) - Frost, Holly M.; Keith, Amy; Sebastian, Thresia; Jenkins, Timothy C.
Abstract: Surveyed caregivers of children in Denver, Colorado, with acute otitis media (AOM) preferred immediate antibiotics over delayed antibiotics or observation. Overall, 77% stated that they would immediately fill a prescription written as delayed. In contrast, 86% of caregivers favored whichever duration was recommended by the provider or the shortest duration necessary.